Speech and harm : controversies over free speech - Maitra, Ishani; McGowan, Mary Kathryn, 1968- (Oxford, U.K. : Oxford University Press, 2012)
"Most liberal societies are deeply committed to a principle of free speech. At the same time, however, there is evidence that some kinds of speech are harmful in ways that are detrimental to important liberal values, such as social equality. Might a genuine commitment to free speech require that we legally permit speech even when it is harmful, and even when doing so is in conflict with our commitment to values like equality? Even if such speech is to be legally permitted, does our commitment to free speech allow us to provide material and institutional support to those who would contest such harmful speech? And finally, and perhaps most importantly, which kinds of speech are harmful in ways that merit response, either in the form of legal regulation or in some other form? This collection explores these and related questions. Drawing on expertise in philosophy, sociology, political science, feminist theory, and legal theory, the contributors to this book investigate these themes and questions. By exploring various categories of speech (including pornography, hate speech, Holocaust denial literature, "Whites Only" signs), and attending to the precise functioning of speech, the essays contained here shed light on these questions by clarifying the relationship between speech and harm. Understanding how speech functions can help us work out which kinds of speech are harmful, what those harms are, and how the speech in question brings them about. All of these issues are crucially important when it comes to deciding what ought to be done about allegedly harmful speech."--Publisher's website.
Introduction and overview / Ishani Maitra and Mary Kate McGowan -- Freedom of expression and human rights law : the case of Holocaust denial / Andrew Altman -- 'Speaking back' : the likely fate of hate speech policy in the United States and Australia / Katharine Gelber -- Beyond belief : pragmatics in hate speech and pornography / Rae Langton -- Subordinating speech / Ishani Maitra -- On 'whites only' signs and racist hate speech : verbal acts of racial discrimination / Mary Kate McGowan -- Power in public : reactions, responses, and resistance to offensive public speech / Laura Beth Nielsen -- Genocidal language games / Lynne Yirrell -- Words that silence? Freedom of expression and racist hate speech / Caroline West.
Includes bibliographical references and index.
Keywords: Freedom of speech -- Social aspects